Magnetite@MCM‐41 nanoparticles as support material for Pd‐N‐heterocyclic carbene complex: A magnetically separable catalyst for Suzuki–Miyaura reaction. (17th March 2021) - Akkoç, Mitat; Buğday, Nesrin; Altın, Serdar; Yaşar, Sedat
Abstract : The Magnetite@MCM‐41@NHC@Pd catalyst was obtained with Pd metal bound to the NHC ligand anchored to the surface of Fe3 O4 @MCM‐41. It was characterized by Fourier transform infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), energy disperse X‐ray analysis (EDX), thermogravimetric analysis (TGA), differential thermal analysis (DTA), and scanning electron microscopy (SEM). The amount of Pd in the Magnetite@MCM‐41@NHC@Pd was measure by inductively coupled plasma–optical emission spectroscopy (ICP‐OES) analysis. The catalytic activity of Magnetite@MCM‐41@NHC@Pd heterogeneous catalyst done on Suzuki–Miyaura reactions of aryl halides with different substituted arylboronic acid derivatives. All coupling reactions afforded excellent yields and up to 408404 Turnover Frequency (TOF) h −1 in the presence of 2 mg of Magnetite@MCM‐41@NHC@Pd catalyst (0.0564 mmol g −1, 0.01127 mmol% Pd) at room temperature in 2‐propanol/H2 O (1:2). Moreover, Magnetite@MCM‐41@NHC@Pd catalyst was recover by applying the magnet and reused for another reaction. The catalyst showed excellent structural and chemical stability and reused ten times without a substantial loss in its catalytic performance. Abstract : The Magnetite@MCM‐41@NHC@Pd catalyst was synthesized and applied as catalyst on Suzuki–Miyaura cross‐coupling reactions. All coupling reactions afforded excellent yields with up to 408404 TOF h −1 .